Dampak Surat Keputusan Nomor 463/Menhut-Ii/2013 tentang Hutan Lindung di Kota Batam - Lu Sudirman; Candy Candy (Journal of Judicial Review, 2016)
Batam City wellknown as industrial area which the populations has growth rapidly over recent decade. When the urbans area became crowded, the demand for landhousing obviously will also increase. There some problem related to the status of the conservations forest in the Batam City after the enactment of the Decree of the Minister of Forestry Number 463/Menhut-II/2013. This research seeks to analyze the effect of the decree for protected forrest and legal certainty of the landrights in Batam. This research uses normative-empirical legal research by case approach. Data used in the form of primary data as supporting research and secondary data. Data were collected by interview and library research. Based on this study, the Decree of the Minister of Forestry Number 463/Menhut-II/2013 don’t allow the area which included conservations forest toissue the land certificate. As a consequence the policy rise the legal uncertainty and disadvantage for some societies in Batam City, while the legal certainty of the status of land rights before the decree remain in force as appropriate.